Letter from Strickland Kneass to to James Curtis Booth - Kneass, Strickland (1863)
Strickland Kneass, an Philadelphian engineer and son of engraver of the U.S. Mint, writes to James Curtis Booth (1810-1888) seeking permission to open the well of the church adjoined to the Mint.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Kneass, Strickland, 1821-1884